(untitled) (PerCursos, 2024)
Oswaldo de Camargo began publishing literature in 1958 and, since then, has stood out for his longevity in more than sixty years of literary activity with a work consisting of different genres, presenting, as one of its characteristics, care for the memory of history of literature and black Brazilian authors. Thus, Camargo published poetry anthologies, a history of black Brazilian literature, essay books dedicated to black authors and also explored this memorialistic bias in his fiction. This article investigates the importance of black literary memory and the records in his essays, fiction books and the poetry anthology organized by him, relating these works to the singularity of Oswaldo de Camargo’s literary life, capable of providing the possible conditions to combat oblivion and invest in the presence of black people in Brazilian literature.